Можливості залучення імовірнісного аналізу безпеки для фізичного захисту ядерних установок - Горбачик, Сергій Олегович; Клевцов, Сергій Валерійович (Національний технічний університет "Харківський політехнічний інститут", 2023)
Представлено аналіз можливості використання такого інструменту, як імовірнісний аналіз безпеки атомних електростанцій для кількісної оцінки рівня фізичного захисту ядерних установок. Впровадження даного інструменту дозволить суттєво підвищити стан фізичної ядерної безпеки та наддасть можливість визначити критичні проблеми в системах фізичного захисту від зовнішніх та внутрішніх правопорушників. На основі проведення імовірнісного аналізу безпеки для фізичного захисту ядерних установок можливо здійснити процес модернізації систем фізичного захисту, приймаючи до уваги, як економічні, так і захисні можливості для раціонального розподілення ресурсів.

The purpose of this study is to analyze the applicability of probabilistic analysis of the safety of nuclear power plants for the quantitative evaluation of nuclear security level of nuclear facilities. Such a tool as probabilistic safety analysis has shown itself to be excellent in identifying the sources of the accident, predicting the progress of the accident and emergency processes that are related to the operation of equipment used directly in the operation of reactors. Therefore, if a probabilistic analysis is implemented for the physical protection of nuclear facilities, it will make it possible not only to identify previously unknown critical vulnerabilities, but also to rationally allocate material and human resources to achieve the appropriate level of physical protection of nuclear facilities. After analytical observations and research, it is planned to conduct a calculation process based on the development of a methodology and procedure for the analysis of the success criteria of the probabilistic analysis of nuclear security.
Possibilities of involving probabilistic safety analysis for physical protection of nuclear facilities
Keywords: фізичний захист; ядерна захищеність; імовірнісний аналіз безпеки; неправомірне вилучення ядерних матеріалів; радіаційна безпека; критерії успіху; диверсія; physical protection; nuclear security; probabilistic safety analysis; illegal extraction of nuclear materials; radiation safety; success criteria; sabotage